2013
DOI: 10.1186/1742-4690-10-78
|View full text |Cite
|
Sign up to set email alerts
|

Changes in codon-pair bias of human immunodeficiency virus type 1 have profound effects on virus replication in cell culture

Abstract: BackgroundHuman immunodeficiency virus type 1 (HIV-1) has a biased nucleotide composition different from human genes. This raises the question of how evolution has chosen the nucleotide sequence of HIV-1 that is observed today, or to what extent the actual encoding contributes to virus replication capacity, evolvability and pathogenesis. Here, we applied the previously described synthetic attenuated virus engineering (SAVE) approach to HIV-1.ResultsUsing synonymous codon pairs, we rationally recoded and codon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
90
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(98 citation statements)
references
References 38 publications
6
90
0
2
Order By: Relevance
“…It has previously been demonstrated that large-scale re-encoding generates attenuated viruses and the studies support the proposal that relative degree of attenuation or replicative fitness can be regulated by modulating the number of introduced synonymous mutations [18,19,20,21,22,23,24,25,26,27]. Indeed, a re-encoded strain of influenza A virus that displayed limited fitness in cellulo was highly attenuated when tested in a mouse model and showed potential for use as a vaccine candidate [25].…”
Section: Discussionmentioning
confidence: 52%
“…It has previously been demonstrated that large-scale re-encoding generates attenuated viruses and the studies support the proposal that relative degree of attenuation or replicative fitness can be regulated by modulating the number of introduced synonymous mutations [18,19,20,21,22,23,24,25,26,27]. Indeed, a re-encoded strain of influenza A virus that displayed limited fitness in cellulo was highly attenuated when tested in a mouse model and showed potential for use as a vaccine candidate [25].…”
Section: Discussionmentioning
confidence: 52%
“…Four synthetic live RSV mutants were designed and readily recovered. It is noteworthy that Min FLC was readily recovered even though 9 of the 11 RSV ORFs (representing almost 94% of the protein-coding sequence) in this virus had been subjected to CPD; for comparison, to date, CPD has been reported for substantially smaller regions of the genomes of poliovirus or HIV-1 (∼23% and 4% of the proteincoding sequence, respectively) or influenza virus (three segments out of eight) (5,10,11,13).…”
Section: Discussionmentioning
confidence: 93%
“…Because amino acid coding is unaffected, CPD strains provide the same repertoire of epitopes for inducing cellular and humoral immunity as the WT pathogen. Recently, the CPD approach has been used successfully to attenuate poliovirus, influenza A virus, Streptococcus pneumonia, and HIV type 1 (5,(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…However, alternative mechanisms involving the induction of innate immunity as a result of changing dinucleotide frequency have been proposed by other authors (23). Furthermore, codon pair bias deoptimization of other viruses, including respiratory syncytial virus (RSV) (24), human immunodeficiency virus type 1 (25), dengue virus (26), and vesicular stomatitis virus (27), have also led to attenuated strains. All these reports indicate that codon and codon pair bias deoptimization can also be a useful tool to develop attenuated vaccine candidates against RNA viruses.…”
Section: Foot-and-mouth Disease (Fmd) Ismentioning
confidence: 99%